Market Structure and Innovation Policies in Switzerland - Dal Zotto, Cinzia; Schenker, Yoann (Nijmegen, The Netherlands Radboud University, 2015)
In: Hans van Kranenburg (Ed.), A European Comparison of Innovation Policies to Trigger Innovation in Journalism and News Media, Research Report